Morphological findings of arteriolar atherosclerosis and prognosis in patients undergoing artery bypass grafting in Armenia - Kukurtchyan, Nona; Karapetyan, Gohar; Kocharyan, Arman; Voskanyan, Mher; Hovhannisyan, Mamicon (Medical Research Archives, 2025)
Cardiovascular disease remains the leading global cause of mortality and morbidity. Atherosclerotic alterations play a pivotal role not only in coronary vessels but also within the microcirculatory system, particularly affecting arterioles. Right atrial appendage specimens from patients with coronary artery disease (CAD), obtained during cardiac surgical interventions, were processed using transmission electron microscopy (TEM), stained with Azure- 2, and examined under a light microscope. Morphological analysis revealed a marked increase in arteriolar formation via the intussusceptive angiogenesis mechanism. In certain patients, the number of de novo arterioles reached 4 points on a 5-point pathological vascular growth scale for intussusceptive angiogenesis. Coronary artery bypass grafting (CABG) is generally indicated for patients presenting with the most advanced forms of ischemic heart disease (IHD). Arteriolar atherosclerosis in CAD may represent one of the underlying mechanisms contributing to heart failure. Early detection of such pathological changes may facilitate prognostication of disease progression, estimation of life expectancy, and the selection of optimal therapeutic strategies.